Ion precipitation in the cusp for northward IMF and its relationship with magnetosheath flow - Haruto Koike; Satoshi Taguchi (Earth, Planets and Space, 2024)
Abstract If the interplanetary magnetic field (IMF) has a northward component, a portion of the solar wind ions flowing in the high-latitude magnetosheath drastically alters the flow direction owing to lobe reconnection and follows the Earth's magnetic field lines toward the low-altitude cusp. Partly because of this folded path, the relationship between the speed of ion flow in the magnetosheath and the energy of the precipitating ions in the low-altitude cusp remains unclarified. Herein, we examined particle data from 11 years of observations by Defense Meteorological Satellite Program satellites to obtain 1990 cases through an automated event identification of the cusp. This corresponds to the largest number of cusp ion events reported to date for a stable northward IMF. The results revealed a positive correlation between the energy of the precipitating ions and the estimated flow speed in the magnetosheath, which answers the question that has remained unexplained for decades: why is the brightness of the cusp proton aurora more strongly correlated with the solar wind dynamic pressure than with the solar wind number density? We suggest additional energizations of the exhausted ions from lobe reconnection in the outflow region because of the turbulent electric field formed by the opposite flow of two ion populations—one in the tailward-directed magnetosheath flow and the other in the earthward-directed outflow jet. Graphical Abstract